Evaluation of oral mucosa collagen condition with cross‐polarization optical coherence tomography. Issue 4 (5th July 2012) - Gladkova, Natalia; Kiseleva, Elena; Robakidze, Natalia; Balalaeva, Irina; Karabut, Maria; Gubarkova, Ekaterina; Feldchtein, Felix
Abstract The goal of the research was analysis of the effect of collagen condition in formation of cross‐polarized CP OCT images. We used of the CP OCT technique for studying collagen condition on an example of oral mucosa. Special histologic picrosirius red (PSR) staining of cheek mucosa specimens was used with subsequent assessing of the result of collagen staining in polarized light. High correlation (r = 0.692, p = 0.0001) between OCT signal standard deviation (SD) in cross‐polarized images and brightness of PSR stained collagen fibers in cheek mucosa specimens was demonstrated in patients with inflammatory intestine and oral mucosa diseases. We have found that the OCT signal SD in cross‐polarized images reflects two boundary conditions of collagen disorganization, namely, loss of fiber properties at active inflammation which attenuates the signal and fibrosis that occurs due to synthesis of a new remodeled collagen which amplifies the OCT signal. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)